All solid-state lithium–oxygen batteries with MOF-derived nickel cobaltate nanoflake arrays as high-performance oxygen cathodes. Issue 72 (21st August 2019) - Gong, Hao; Xue, Hairong; Lu, Xueyi; Gao, Bin; Wang, Tao; He, Jianping; Ma, Renzhi
Abstract : Solid-state lithium oxygen batteries with MOF-converted nickel cobaltate nanoflake arrays as high-performance oxygen cathodes were prepared, delivering high reversibility and long-term cycling stability over 90 cycles. Abstract : Solid-state Li1+ x Al x Ge2− x (PO4 )3 electrolytes with high ionic conductivity were prepared and successfully applied in lithium–oxygen batteries (LOBs). Combined with MOF-derived NiCo2 O4 cathodes, the solid-state LOBs deliver a high discharge capacity and good rate performance. Moreover, enabled by such a bifunctional cathode, the as-assembled solid-state LOBs show enhanced reversibility and long-term cycling stability over 90 cycles.